HOW HELPFUL THE WRITERS ARE: A CORPUS-ASSISTED DISCOURSE STUDY OF ONLINE REVIEWS OF TOURIST ATTRACTIONS - Rika Mutiara (International Journal of Humanity Studies (IJHS), 2018)
The use of corpus methods that combines both quantitative and qualitative aspects has benefited the field of discourse analysis. It is a corpus-assisted discourse study. The study focuses on the ways the writers of online reviews of tourist attractions in TripAdvisor website interact and how they position themselves and the readers. The study employed Lextutor online to get the keywords and Antconc to find the collocations and scrutinize the concordance lines. In the interaction, the writers evaluated the tourist attractions, gave advice and instructions, recounted, reported what the others said, thanked, and encouraged the readers to imagine. The writers tried to provide the information as much as possible and put themselves as the ones that have wider knowledge than the readers. They did it to help the readers make the right decision and anticipate particular conditions. A particular language structure such as prepositional phrases becomes the salient features of this text type.